Dampak keterlibatan konten digital terhadap pengalaman pelanggan daring melalui kepercayaan dan sikap - Tissa Aulia Damayanti; Christianingrum Christianingrum; Sumar Sumar (Jurnal Manajemen Maranatha, 2025)
In response to the growing influence of short-form video in Indonesia’s digital marketing landscape, this study explores how digital content engagement on TikTok affects online customer experience (OCE), using the case of the local skincare brand Somethinc. The research investigates both direct and mediated effects of content engagement categorized into consumption, contribution, and creation OCE, with customer trust and consumer attitude as mediators. Employing a quantitative, causal-explanatory design, data were collected from 437 active TikTok users who follow @somethincofficial through an online survey. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to test the hypothesized relationships. The findings demonstrate that digital content engagement positively influences OCE not only directly, but also indirectly through trust and attitude. Customer trust functions as a psychological enabler that deepens the relationship between engagement and experience, while consumer attitude acts as a filter translating users’ cognitive and affective responses into evaluative outcomes. The model meets the criteria for construct reliability, convergent, and discriminant validity. An R² value of 43.5% for OCE indicates a substantial explanatory capability. These results underscore the importance of producing content that not only attracts interactions but also fosters credibility and emotional connection. Marketers should emphasize content that is informative, authentic, and visually appealing to cultivate trust and favorable attitudes, ultimately enhancing the digital journey. This study contributes to theory by embedding psychological mediators into the COBRAs framework and reinforces TikTok’s strategic role in shaping comprehensive brand experiences. Future studies may expand to other platforms and methodological approaches.